At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To find the value of \( y \) that makes the equation \( y = -2x + 4 \) true when \( x = 1 \), we will substitute \( x = 1 \) into the equation and solve for \( y \). Here are the steps in detail:
1. Start with the given equation:
[tex]\[ y = -2x + 4 \][/tex]
2. Substitute \( x = 1 \) into the equation:
[tex]\[ y = -2(1) + 4 \][/tex]
3. Perform the multiplication first:
[tex]\[ y = -2 \cdot 1 + 4 \][/tex]
[tex]\[ y = -2 + 4 \][/tex]
4. Then, perform the addition:
[tex]\[ y = 2 \][/tex]
So, the value of \( y \) that makes the equation true when \( x = 1 \) is \( y = 2 \).
Therefore, the correct answer is:
C) 2
1. Start with the given equation:
[tex]\[ y = -2x + 4 \][/tex]
2. Substitute \( x = 1 \) into the equation:
[tex]\[ y = -2(1) + 4 \][/tex]
3. Perform the multiplication first:
[tex]\[ y = -2 \cdot 1 + 4 \][/tex]
[tex]\[ y = -2 + 4 \][/tex]
4. Then, perform the addition:
[tex]\[ y = 2 \][/tex]
So, the value of \( y \) that makes the equation true when \( x = 1 \) is \( y = 2 \).
Therefore, the correct answer is:
C) 2
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.